Assessment of the Effectiveness of Programs put in place to Control Students’ Absenteeism in Public Day Secondary Schools in Kirinyaga County, Kenya - Gitonga , Leah M.; Njoka , Johannes N.; Lucy , Ndegwa (African Journal of Education,Science and Technology (AJEST), 2018)
This paper assessed the effectiveness of programs put in place to curb absenteeism by learners in public day secondary schools in Kirinyaga County, Kenya. The study adopted a descriptive survey research design. The target population included 79 principals and 317 teachers in public secondary schools in Kirinyaga County. The researcher employed the Gay formula of 20 per cent to select a sample of 16 principals and 63 teachers. Data was collected by means of a questionnaire administered to the sampled principals and teachers. Content validity of the instrument was ascertained by expert opinion, while reliability was assessed by Cronbach coefficient alpha technique which yielded a correlation coefficient of 0.71 for the instrument. The collected data was analyzed using descriptive statistics with the help of the Statistical Package for Social Sciences (SPSS) Version 20.0. Data analysed using Statistical Package for Social Sciences (SPSS) Version 20.0 revealed that in majority of schools affordable school levies, bursaries and spot checks and roll calls were effective in reduction of students’ absenteeism. However, the study further established that guidance and counseling was not an effective intervention in addressing learner absenteeism in public day secondary schools. On the basis of the findings of this study, it is recommended that schools adhere to the fees guidelines as stipulated by the ministry of education, education stakeholders should enhance the provision of bursaries to needy students and that teachers consistently mark class registers to capture students attendance to all instructional sessions in every school day. Lastly, there is need to enhance guidance and counseling programmmes in order to make them effective in addressing absenteeism among learners.